A two-scale finite element model for the fatigue design of large welded structures. (June 2021) - Heyraud, H.; Robert, C.; Mareau, C.; Bellett, D.; Morel, F.; Belhomme, N.; Dore, O.
Highlights: A numerical two-scale approach is proposed to model large welded structures. This approach combines solid and shell finite elements to model weld details. A condensation procedure is used to significantly reduce the computational cost. The proposed strategy allows computing a non-local multiaxial fatigue criterion. The stiffness of weld details is correctly evaluated with the two-scale approach. Abstract: Weld toes and weld roots of continuously welded structures subjected to cyclic loading are critical zones in terms of the fatigue resistance. The finite element method coupled with a fatigue criterion is commonly used to ensure the correct sizing and fatigue design of welded structures. However, weld geometries are often simplified or idealized to limit computational cost. In this work, a numerical two-scale approach is proposed in order to calculate a non-local multiaxial equivalent stress at the weld toe and the weld root from a global finite element shell model. The influence of the parameters of the proposed model on the stiffness behaviour is investigated for three welded structures and for different loading cases. A comparison in terms of stiffness with other models from the literature is also proposed. The results show that the stiffness behaviour is not affected by the parameters of the proposed approach and that it is the most robust model for the different geometries and loading cases studied. The variation in the non-local multiaxial equivalent stress as a function of the parameters of the proposed approach was also studied. The comparison with full solid finite element models makes it possible to define minimum values for the different parameters studied and validates the potential of the proposed approach for the fatigue design of welded structures.